Linear Average Yield Criterion and Its Application in Failure Pressure Evaluation of Defect-Free Pipelines - Jian-Hong Ji; Ming-Ming Sun; Jie Zhang (Technologies)
Analysis of internal pressure failure is a crucial aspect of assessing pipeline integrity. By combining the unified yield criterion with actual burst data, the applicability of different yield criteria is elucidated. Based on the distribution law of burst data, a linear average yield criterion is proposed. The results indicate that the yield function of the linear average yield criterion is a linear expression, and the yield path forms an equilateral non-equiangular inscribed dodecagon within the von Mises circle. For the evaluation of failure pressure, this yield criterion exhibits the highest level of applicability, followed by the ASSY and Tresca yield theories. The linear average yield criterion limits the failure pressure prediction error, with low strain-hardening (0 ≤ n ≤ 0.06) to within 3%.